Justice Could Be Highlighted in the Perspective of Historical Materialism - Xu, Guowang; Zheng, Wei (Scientific Research Publishing, 2016)
How to understand the relationship between historical materialism and Marx’s idea of justice? The well-know Canadian philosopher, Kai Nielsen, “who is indeed closer to Marxist moralism in substantive conclusion, but, methodologically speaking, it is more in the spirit of Marxist immoralism” (Nielsen,1987: p. 114), points out Marx’s ideological system is not a valueless theory of science and society, and the facts and value judgments can be unified in Marx’s theory. Nielsen reveals the profound idea of justice as the basic dimension of historical materialism, and the internal unity of fact judgment and value judgment in a dual dimensions, based on the perspective of historical materialism, showing “justice could be highlighted in the perspective of historical materialism”.
Keywords: Historical Materialism; Marx’s Idea of Justice; Fact Judgment; Value Judgment